ANALISIS PENGAKUAN PENDAPATAN BERDASARKAN PSAK NOMOR 72 PADA PT. ISRA PRESISI INDONESIA Tbk - Rohmatun, Rohmatun (Politeknik Negeri Ambon, 2023)
Revenue is one of the signs of profit in a company. This study aims to determine whether the accounting practices in revenue recognition at PT Isra Presisi Indonesia are in accordance with the Statement of Financial Accounting Standards (PSAK) Number 72 or not. This research is included in the type of quantitative research with a descriptive approach. The data used is secondary data in the form of the company's annual financial statements obtained from the Indonesia Stock Exchange (IDX) website. Based on the results of the study, it is found that revenue recognition at PT Isra Presisi Indonesia is in accordance with the Statement of Financial Accounting Standards (PSAK) Number 72.